THE ROLE OF MEDIA COVERAGE ON THE INFLUENCE OF CORPORATE GOVERNANCE, RISK MANAGEMENT DISCLOSURE, AND FINANCIAL DISTRESS ON REAL EARNINGS MANAGEMENT IN TRANSPORTATION COMPANIES LISTED IN THE INDONESIAN RUPIAH - Prisela, Prisela; Rahayu, Putri; Komara, Acep (Ridwan Institute, 2024)
This study aims to investigate the impact of media attention, corporate governance, risk management disclosures, and financial crises on the real profit management practices of the transportation industry on the Indonesia Stock Exchange (IDX) in 2020 and 2022. This study uses secondary data and targeted sampling techniques. The transportation industry's annual financial statements 2020-2022 and business reports available on the IDX website were used in this study. The independent variables, UDD, KA, RMD, MC, and FD, simultaneously had a significant effect on REM, according to a significance value of F of 0.021 or less than the probability value (p-value) of 0.05 (0.021 0.05). The results of this study imply that larger boards may be less likely to engage in profit management, especially in the transportation sector. This indicates that the ability of the audit committee to mitigate real-based profit management may be limited. Media publicity has no effect on real profit. Moreover, longitudinal studies on the effects of financial crisis on profit management could provide insights into how different phases of crises impact profit management over time.